Advances in CrossBoss/Stingray use in antegrade dissection reentry from the Asia Pacific Chronic Total Occlusion Club. Issue 7 (26th November 2019) - Wu, Eugene B.; Brilakis, Emmanouil S.; Lo, Sidney; Kalyanasundaram, Arun; Mashayekhi, Kambis; Kao, Hsien‐Li; Lim, Soo‐Teik; Ge, Lei; Chen, Ji‐Yan; Qian, Jie; Lee, Seung‐Whan; Harding, Scott A.; et al.
Abstract: Antegrade dissection reentry with Stingray device (Boston Scientific, Marlborough, MA) accounts for 20–34% of the chronic total occlusion (CTO) cases in the various hybrid operators' CTO registries and is an important component of CTO crossing algorithms. The Stingray device can facilitate antegrade dissection and reentry, however its use is low outside North America and Europe. The Asia Pacific CTO Club along with three experience Stingray operators from the US, Europe and India, created an algorithm guiding use of the CrossBoss and Stingray catheter. This APCTO Stingray algorithm defines when to use the CrossBoss and Stingray device recommending a reduction in CrossBoss use except for in‐stent restenosis lesions and immediate transition from knuckle wiring to the Stingray device. When antegrade wiring fails, choice of Stingray‐facilitated reentry versus parallel wiring depends on operator experience, device availability, cost concerns, and anatomical factors. When the antegrade wire enters the subintimal space, we recommend using a rotational microcatheter to produce a channel and deliver the Stingray balloon—so called the "bougie technique." We recommend early switch to Stingray rather than persisting with single wire redirection or parallel wire. We recommend choosing a suitable reentry zone based on preprocedural computer tomography or angiogram, routine use of stick and swap, routine use of Subintimal TRAnscatheter Withdrawal (STRAW) through the Stingray balloon, and the multi stick and swap technique. We believe these techniques and algorithm can facilitate incorporation of the Stingray balloon into the practice of CTO interventionists globally.